Теоретичні дослідження режимів і параметрів метантенку біогазової установки - Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Skliar, Oleksandr; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Skliar, Radmila (ТДАТУ, 2020)
В статті обґрунтовано режими і параметри метантенку біогазової установки для підвищення ефективності переробки пташиного посліду. Доведено, що одна з основних завдань щодо обґрунтування режиму біогазових установок – визначення оптимальної тривалості переробки посліду в метантенку. Отримано формулу для її визначення, яка показує залежність оптимальної тривалості переробки від вартості одержуваного тепла, енергії згоряння біогазу та вартості утилізації посліду. З урахуванням наведених допущень, обґрунтовано мінімальну витрату металу на стінки метантенку при висоті конусу, яка дорівнює 2,4 м. Доказано, що на відміну від коефіцієнта тертя, вартості посліду та вартості одного Джоуля енергії, на форму метантенку впливають насамперед витрати, що пов'язані з виробництвом його корпусу. В статье обоснованы режимы и параметры метантенка биогазовой установки для повышения эффективности переработки птичьего помета. Доказано, что одна из основных задач по обоснованию режима биогазовых установок - определение оптимальной продолжительности переработки помета в метантенке. Получена формула для ее определения, которая показывает зависимость оптимальной продолжительности переработки от стоимости получаемого тепла, энергии сгорания биогаза и стоимости утилизации помета. С учетом приведенных допущений, обоснован минимальный расход металла на стенки метантенка при высоте конуса, равной 2,4 м. Доказано, что в отличие от коэффициента трения, стоимости помета и стоимости одного Джоуля энергии, на форму метантенка влияют прежде всего расходы, связанные с производством его корпуса. The article explains the modes and parameters of the digester of a biogas plant to improve the efficiency of processing poultry manure. The experience of operating such plants is negligible, and the decision of technological problems without critical thinking follow the installation of new generations, so there is a contradiction between the theory of the process of anaerobic fermentation of manure to produce biogas and fertilizers and methods of construction and calculation of technical means for its implementation. The intensity of digestion it is possible to increase the mechanical splitting and destruction of the structure of solid organic components or mechanical destruction, which leads to an increase of the active surface, which is processed metanetwork microorganisms, destroying cells and releasing capable of intracellular digestion liquid containing soluble organic matter. It is proved that one of the main problems of the substantiation of the regime of biogas plants – determination of the optimal duration of processing of dung in the digester: long enough to make manure in anaerobic conditions leads to incomplete manure, excessively long processing reduces the mass of litter disposed of during the year and leads to economic losses. The formula for determining the optimal duration of manure, which shows that it depends on the cost of heat obtained, of the energy of combustion of biogas and the cost of utilization of dung. Given the above assumptions, reasonably minimal amount of metal on the walls of the digester at the height of the cone, which is equal to 2.4 m. it is Proved that in contrast to the coefficient of friction, cost of manure and cost of one Joule of energy, in the form of digester is primarily influenced by the costs associated with the production of his body.
Теоретические исследования режимов и параметров метантенка биогазовой установки
Theoretical research of the modes and parameters of the biogase mechanical installation
Keywords: біогазова установка; метантенк; пташиний послід; бродіння; тривалість переробки; біогаз; добриво; биогазовая установка; метантенк; птичий помет; брожение; продолжительность переработки; биогаз; удобрения; biogas plant; digester; bird droppings; fermentation; duration of processing; biogas; fertilizer